Morphine to relieve exertional dyspnoea in COPD: myth, dream or reality?. Issue 4 (19th October 2017) - Laviolette, Louis; Laveneziana, Pierantonio
Dyspnoea, "the subjective experience of breathing discomfort that consists of qualitatively distinct sensations that vary in intensity" [1], is ever present in patients with chronic obstructive pulmonary disease (COPD) and affects almost all aspects of their daily lives [2]: up 60% of patients have limitations in normal physical activity and more than a third are restricted in family activities [2]. Dyspnoea is usually the earliest and most troublesome complaint for which these patients seek medical attention. As the underlying disease advances, dyspnoea progresses relentlessly, invariably leading to a gradual decrease in activity levels and associated skeletal muscle deconditioning and impoverished quality of life [2]. Dyspnoea also has strong prognostic value for mortality: stronger than the forced expiratory volume in 1 s in patients with COPD or angina in patients with heart disease [3, 4]. Opioids show promise in managing exertional dyspnoea; safety of widespread use in COPD patients remains unproven http://ow.ly/A9bX30fr7FR